Short report: Evaluating the safety and usability of head-mounted virtual reality compared to monitor-displayed video for children with autism spectrum disorder. (October 2020) - Malihi, Mahan; Nguyen, Jenny; Cardy, Robyn E; Eldon, Salina; Petta, Catharine; Kushki, Azadeh
Virtual reality provides a relatively inexpensive way to learn and repeatedly practice skills in personalized, controlled, and safe computer-generated settings. These systems are increasingly receiving attention as an innovative medium for delivering interventions to children with autism spectrum disorder. Although many virtual reality systems are commercially available and their use is increasing, little is known about the safety and usability of these systems for children with autism spectrum disorder. The aim of this study was a first step in addressing this gap. A convenience sample of 35 children with a diagnosis of autism spectrum disorder participated in an immersive head-mounted display virtual reality experience and a control condition (monitor-displayed video). Levels of anxiety and negative effects experienced were not significantly different between the two conditions. Participants reported significantly enhanced spatial presence (p = 0.003; d = 0.3) and naturalness (p = 0.002; d = 0.47) for the head-mounted display–virtual reality condition, and 74% of participants preferred using head-mounted display–virtual reality over monitor-displayed video. These findings provide preliminary evidence to support the safety and usability of head-mounted display–virtual reality for children with autism spectrum disorder. Future studies are needed to replicate the results in a larger sample, a range of virtual reality experiences, and in the context of long-term exposure. Lay abstract: This study investigated the safety and usability of a virtual reality experience for children with autism spectrum disorder in a laboratory setting. In our study, the negative effects of head-mounted display–virtual reality were similar to monitor-displayed video watching. At the same time, the participants indicated that the head-mounted display–virtual reality experience provided improved realism and sense of presence. This study is a first step in understanding the impact of head-mounted display on children with autism spectrum disorder.